"Doing What Only I Can Do": Experiences From Participating in a Multimodal Exercise-Based Intervention in Older Patients With Advanced Cancer—A Qualitative Explorative Study. Issue 2 (21st March 2022) - Mikkelsen, Marta Kramer; Michelsen, Hanne; Nielsen, Dorte Lisbet; Vinther, Anders; Lund, Cecilia Margareta; Jarden, Mary
Abstract : Background: Sparse evidence exists regarding the feasibility and patients' experiences of exercise programs among older cancer populations. Objective: The aim of this study was to explore the experiences of older patients with advanced cancer who participated in a 12-week supervised and multimodal exercise program in a hospital setting. Methods: Individual interviews were conducted with 18 participants (≥65 years) with advanced cancer who completed the intervention program regardless of compliance rate. In addition, written evaluation questionnaires were collected. Data were analyzed using thematic analysis. Results: Three main themes were identified: (1) Motivated to strengthen body and mind, with the subthemes "Doing what only I can do" and "Reaching goals with support from healthcare professionals and peers"; (2) Exercise as an integrated part of the treatment course ; and (3) Overcoming undeniable physical limitations . Conclusions: The participants experienced several benefits from participation, including physical improvements, increased energy, reduction of symptoms, and improved social engagement. Goal setting, being positively pushed and cheered on, and integration of fun games increased motivation. In contrast, being pushed beyond physical limitations and experiencing severe symptoms were experienced as barriers toward exercising. Adherence to the exercise program was facilitated by coordinating a tailored program with medical appointments and receiving comprehensive support and guidance. Implications for Practice: Multimodal exercise programs seem to be beneficial for older patients with advanced cancer and should be coordinated with oncological treatment in combination with targeted support and advice on symptom management.